Computer-Assisted Verification Method for Invariant Densities and Rates of Decay of Correlations - Ippei, Obayashi (SIAM journal on applied dynamical systems, 2011)
A new computer-assisted verification method for invariant densities and decay rates of correlations is proposed. This new method is based on the Hilbert cone technique. [PUBLICATION ABSTRACT]